The Effect of Structured Discharge on Family Readiness to Provide Transient Care for Stroke Patients - Tri antika rizki kusuma Putri; Riza Sukma Agustian; Suci Noor Hayati; Gina Nurdina; Tri Hapsari Retno Agustina; Susy Puspasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Every situation that occurs in the ICU, whether in critical conditions or life-threatening conditions, can make the patient's family feel anxious. A combination of natural relaxation sounds and deep breathing relaxation is one of the non-pharmacological therapies that could help reduce anxiety Purpose: Understanding the effect of the combination of natural relaxation sounds and deep breathing relaxation reduces anxiety among families of patients in the waiting room at RSUD'S ICU of Ulin Banjarmasin Methods: With a quasi-experimental pre and post-test without control design using consecutive sampling techniques involving 29 respondent families of patients in the ICU waiting room, the questionnaire utilized the HARS (Hamilton Anxiety Rating Scale). Bivariate analysis employed the Wilcoxon Test to analyze the impact before and after the intervention was administered Result: In the data analysis, a significance value of 0.000 (p < 0.05) was obtained, with Ha accepted, indicating the combination of natural relaxation sounds and deep breathing relaxation can reduce the anxiety levels among families of patients in the waiting room at RSUD'S ICU of Ulin Banjarmasin Implication: The decrease in the anxiety levels among families of patients before and after the intervention with natural relaxation sounds and deep breathing went from severe anxiety (63.3%) to mild anxiety (53.3%). The research results indicated that 10 respondents experienced a decrease in scores of more than 10 points. Therefore, this intervention can be utilized.